Effect of different Chemical Additives on growth of Azotobacter vinelandii - Mounika, N.; Rao, D. Muralidhara; Uma, A.; Ali, SkZ. (International Journal of Scientific Research and Management (IJSRM), 2018)
In this experiment, we evaluated different concentrations of three different chemical amendments viz, polyvinyl pyrrolidone (PVP), gum arabica, and sodium alginate for their ability to support growth and promote survival of Azotobacter vinelandii in nutrient broth during the storage. Azotobacter vinelandiiinoculated with PVP (4%) promoted highest cell population followed by gum arabica (0.5%) and sodium alginate (0.2%).  The results of the present study clearly indicated that the 4% PVP probably gave higher cell population than other additives.